KEARIFAN LOKAL MASYARAKAT DAYAK NGAJU DI KALIMANTAN TENGAH DALAM MELAKUKAN PENYIAPAN LAHAN DENGAN PEMBAKARAN Local wisdom of Dayak Ngaju in Central Kalimantan on Land Preparation by using Fire - Erekso Hadiwijoyo; Bambang Hero Saharjo; Erianto Indra Putra (Jurnal Silvikultur Tropika, 2017)
Dayak Ngaju community used to manage the peat-land for agricultural purposes by the Handel system. The Handel System is a group farming activity in a spesific area along one small river. Land preparation is one of the important step in this system, and Dayak Ngaju community used to do it by fire. Land preparation by burning activity has been done since the very first generation of Dayak Ngaju. There are two important things in land preparation of Dayak Ngaju in Mantangai Village Kapuas Regency, Central Kalimantan, e.g 1) Rules and ritual tradition for land preparation, and 2) the techniques of land-preparation with burning activity. Burning activity should be well-supervised, and there will be a fine (jipen) given if the fire spread uncontrolable and burn the others land. The techniques for land preparation are still in traditional approach, from selected thinning, clearing, and burning activity. Recently there is no appropriate land preparation technology introduced yet, thus make Dayak Ngaju community still highly depend on using fire for their land preparation activity.Key words: handel, land preparation